2020
DOI: 10.1039/c9nr08156a
|View full text |Cite
|
Sign up to set email alerts
|

Designed synthesis of nickel–cobalt-based electrode materials for high-performance solid-state hybrid supercapacitors

Abstract: Schematic descriptions for the formation of CoNi2S4, NiCo-LDH, and NiO/Co3O4 and the excellent electrochemical performance of CoNi2S4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…[ 7 ] : Co 3 O 4 @CoMoO 4 NPF; [ 24 ] Ref. [ 8 ] :CoNi 2 S 4 HSC; [ 55 ] and Ref. [ 9 ] : CoNi‐LDH@PCPs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] : Co 3 O 4 @CoMoO 4 NPF; [ 24 ] Ref. [ 8 ] :CoNi 2 S 4 HSC; [ 55 ] and Ref. [ 9 ] : CoNi‐LDH@PCPs.…”
Section: Resultsmentioning
confidence: 99%
“…Among the TMOs, the Co and Ni oxides have shown high electrochemical activities. 28,29 They can form many different nanostructures providing large surface area, which is significant in capacitors and for electrochemical reactions on the surface of electrodes. 30,31 This combination of pseudocapacitive and electrical double-layer capacitance mechanisms (of energy storage) of these composites can significantly improve their electrochemical performance and catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al reported vertically aligned cobalt oxide nanoparticles on a graphene sheet with the carbon fabric to assemble a flexible asymmetric device with a maximum value of ~580 F g −1 5 . The nickel‐cobalt‐based solid‐state device showed an excellent specific capacitance and cycling stability of 100.7 F g −1 at 1 A g −1 and 132.3% retaining of its primary capacitance after 50 000 cycles, respectively 6 . Xing et al reported vertically grown Ni–Co hydroxide nanosheets on nickel foam by a hydrothermal process for SC applications, and their asymmetric capacitance was 439.5 mF cm −2 at 2 mA cm −2 with excellent stability cycles 7 .…”
Section: Introductionmentioning
confidence: 99%